The Influence of Information Technology on Performance of Accountants in Tripoli, Libya - Shawish, Ahmad Araf Ali (2010)
This study is part of a larger study to explore and community, Factors that affect the organizational culture and adoption of information systems for the oil in Libya and banking sectors, And the results showed that there is a direct relationship between the positive and dimensions of societal culture, And the results showed that there were no differences in the community, Dimensions of culture between the two sectors covered in this study. This means that is affected by the adoption of the culture and community, Other factors that deserve investigation and future implication.